Bronchiolar adenoma/ciliated muconodular papillary tumor mixed with adenocarcinoma in situ in the same tumor. Issue 4 (28th December 2022) - Uchiyama, Suiha; Mizutani, Kenichi; Suzuki, Eriko; Yoshii, Naoko; Watanabe, Takuya; Tsuchida, Hiroyuki; Yobita, Shogo; Iguchi, Kensuke; Nakamura, Minori; Endo, Takumi; Takahashi, Seishiro; Ogawa, Hiroshi; et al.
Abstract: Bronchiolar adenoma (BA)/ciliated muconodular papillary tumor (CMPT) is defined as a benign tumor composed of epithelial and basal cells. Recently, some cases with driver mutations or malignant transformation have been observed. Thus, whether BA/CMPT is benign or malignant remains controversial. We herein report an extremely rare case of a 68‐year‐old woman with a CMPT accompanied by adenocarcinoma in situ (AIS). BA/CMPT existed inside the AIS. The BA/CMPT component did not show any driver mutations; however, the AIS component had an EGFR driver mutation in exon 19. The accumulation of cases and further studies are needed to discuss the malignant potential of BA/CMPT. Abstract : We report an extremely rare case involving mixed BA/CMPT and AIS in the same tumor. In our case, the AIS component had an EGFR driver mutation in exon 19. No driver mutations were detected in the BA/CMPT component. The tumor boundaries between BA/CMPT and AIS were relatively clear. Driver mutations or malignant transformation in BA/CMPT have been reported in several cases, but the present case, it is thought that the two tumors were incidentally mixed. The malignant potential of BA/CMPT should also be considered.